Physical metallurgy of concentrated solid solutions from low-entropy to high-entropy alloys. Issue 6 (December 2017) - Cheng, Chun-Yang; Yang, Ya-Chu; Zhong, Yi-Zhen; Chen, Yang-Yuan; Hsu, Tung; Yeh, Jien-Wei
Highlights: Concentrated solutions are classified with mixing entropy which enhances mixing. Physical metallurgy of concentrated solutions is bridged with that of dilute ones. Lattice distortion effects on physical properties are especially emphasized. Abstract: The alloy world could be divided into low-entropy (LEAs), medium-entropy (MEAs) and high-entropy alloys (HEAs) based on the configurational entropy at the random solution state. In HEAs, four core effects, i.e. high entropy, sluggish diffusion, severe lattice distortion and cocktail effects, are much more significant than low-entropy alloys in affecting phase transformation, microstructure and properties. In fact, the degree of the influence from these core effects more or less increases with increased mixing entropy. The trend is gradual from low-entropy alloys to high-entropy alloys. In this article, physical metallurgy of HEAs is discussed with the bridge connected to that of conventional alloys. As disordered and ordered solid solutions are the main constituent phases of alloys, the understanding of solid solutions is fundamental for the understanding of alloys. In addition, as dilute solid solutions have been well treated in current physical metallurgy, concentrated solid solutions from low-entropy to high-entropy alloys are focused in this article. Physical properties are especially emphasized besides mechanical properties.